2009
DOI: 10.1158/1078-0432.ccr-09-0842
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of the Mammalian Target of Rapamycin Inhibitor Sirolimus and MEC Chemotherapy in Relapsed and Refractory Acute Myelogenous Leukemia

Abstract: Purpose: Inhibiting mammalian target of rapamycin (mTOR) signaling in acute myelogenous leukemia (AML) blasts and leukemic stem cells may enhance their sensitivity to cytotoxic agents. We sought to determine the safety and describe the toxicity of this approach by adding the mTOR inhibitor, sirolimus (rapamycin), to intensive AML induction chemotherapy. Experimental Design: We performed a phase I dose escalation study of sirolimus with the chemotherapy regimen MEC (mitoxantrone, etoposide, and cytarabine) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 36 publications
0
83
0
1
Order By: Relevance
“…PI3K and mTOR inhibitors have now entered clinical trials in AML (Yee et al, 2006;Perl et al, 2009;Chapuis et al, 2010a;Park et al, 2010). However, despite their theoretical potential as antileukaemic agents, their clinical effects have been limited and the reasons for this are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K and mTOR inhibitors have now entered clinical trials in AML (Yee et al, 2006;Perl et al, 2009;Chapuis et al, 2010a;Park et al, 2010). However, despite their theoretical potential as antileukaemic agents, their clinical effects have been limited and the reasons for this are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that higher doses of rapamycin or a combination of mTOR inhibitors may increase the chances of driving these patients into remission [36]. A phase I study examined rapamycin in combination with mitoxantrone, etoposide, and cytarabine in 29 patients with AML [37]. Six of 27 patients who completed chemotherapy experienced a clinical response (complete response [CR] or partial response [PR]).…”
Section: Clinical Studies With Mtor Inhibitors In Leukemiamentioning
confidence: 99%
“…56 Accordingly, previous clinical studies have revealed the low clinical benefit of rapalogs either alone 64 or in combination with high-dose chemotherapies 65 in refractory/relapsed cases of AML. However, although the anti-leukemic activity of the rapalogs has produced largely disappointing results in clinical practice, in vitro studies are ongoing to identify compounds that may function synergistically with them in AML, as reported for the use of histone deacetylases inhibitors (Table 1).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%